Pengaruh Citra, Kepercayaan, dan Tambahan Merek pada Pembelian (Studi Pada Produk Kacang Sembunyi Zaha Barokah) - Muhammad Syarif Hidayatullah Elmas (Ecobuss, 2015)
This study aims to determine the effect on purchases of brand image, brand trust to figure out the effect on the purchase and the additional brand to purchase. The population is the consumers’ of “Kacang Sembunyi Zaha Barokah” products which are 100 respondents. The study used linear regression analysis of multiple with condition test assumption classical by using SPSS 19 software. The linear regression analysis SPSS 19, with multiple software both simultaneously or simultaneously or by partial or each variable (good image trust, and extra brand) influential significantly to variable bound (purchases). Keywords: Brand Image, Brand Trust, an Additional Brand, Purchase